NEUROPHYSIOLOGICAL BASIS OF EMOTIONAL REGULATION: FUNCTIONAL INTERACTIONS BETWEEN THE AMYGDALA AND PREFRONTAL CORTEX (Modern American Journal of Medical and Health Sciences, 2025)
This article provides a detailed analysis of the neurophysiological foundations of emotional regulation, particularly the functional interactions between the amygdala and the prefrontal cortex. The author highlights the central role of the amygdala in the rapid processing of negative emotions and the high-level cognitive control function of the prefrontal cortex. The study discusses “bottom-up” and “top-down” mechanisms, physiological bases of emotional regulation through neuroimaging (fMRI, EEG, DTI), and neurochemical mechanisms (GABA, glutamate, serotonin, dopamine). Furthermore, disturbances within this system in psychopathological conditions such as depression, anxiety disorders, and PTSD, as well as practical therapeutic approaches including cognitive reappraisal, mindfulness, neurofeedback, and transcranial magnetic stimulation (TMS), are examined. The article provides a scientific basis for understanding the biological mechanisms of emotional regulation to support psychotherapy and neurological research.